MASALAH KEAGENAN ALIRAN KAS BEBAS, MANAJEMEN LABA DAN RELEVANSI NILAI INFORMASI AKUNTANSI - Aulia Fuad Rahman (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2011)
Free cash flow agency problem causes potential conflict of interest between managers and shareholders. Managers of firms with high free cash flow and of low growth opportunity tend to invest in marginal or even negative NPV project and use earnings management to camouflage the effects of non-wealth-maximizing investments. As a result, it is predicted that investors will react to earnings management and free cash flow agency problem and therefore reflected in stock price. In this sense, earnings management and free cash flow agency problem is predicted to have an impact on value relevance of accounting information.The objective of this study is to assess the impact of earnings management on value relevance of earnings and book value. This study also investigates the different effect of earnings management on value relevance of earnings and book value between free cash flow agency problem firms and non free cash flow agency problem firms. Result shows that earnings and book value are value relevance and earnings management decreases those value relevances. The result also conclude that the negative effect of earnings management on value relevance of earnings and book value is higher for free cash flow agency problem firms compared to non free cash flow agency problem firms.